Cytotoxic alkaloids against human colon adenocarcinoma cell line (HT-29) from the seed embryos of Nelumbo nucifera - Waraluck Chaichompoo (2018)
© 2017 Springer Science+Business Media, LLC, part of Springer Nature Phytochemical investigation of the CHCl 3 extract of the seed embryos of Nelumbo nucifera Gaertn resulted in the isolation of a new naturally occurring bisbenzylisoquinoline alkaloid, O-methylneferine (1), together with five known alkaloids, neferine (2), armepavine (3), (–)-(1R)-N-methylcoclaurine (4), nuciferine (5), and pronuciferine (6). The structures of these compounds were characterized by spectroscopic methods and comparison of physical properties with those reported in the literature. Among them, compounds 1 and 2 exhibited significant activity against human colon adenocarcinoma cell line (HT-29), with IC 50 values of 0.70 and 1.61 µM, respectively, which were 8- and 3.5-fold higher than that of the reference anticancer drug, doxorubicin (IC 50 5.63 µM). Moreover, compounds 1 and 2 displayed less cytotoxic activity against the non-cancerous HEK 239 cells with the IC 50 values of 42.48 and 12.19 μM, respectively, whereas the cytotoxicity of doxorubicin against this cell line was 0.22 μM. The very potent cytotoxicity against HT-29 cell line and very high selectivity index (60.6-fold) of the alkaloid 1 is of particular significant; it could be considered as a promising structure lead for anti-colon cancer drug development.